MID-TERM RESULTS OF THE ON-PUMP VS OFF-PUMP CORONARY ARTERY BYPASS GRAFTING SURGERY - Mani, Romel; Nardi, Paolo; Bovio, Emanuele; Bassano, Carlo; Pellegrino, Antonio; Chiariello, Luigi (European Scientific Journal, ESJ, 2014)
Objective. To evaluate the fate of ON-pump vs. OP-CABG surgery at mid-term follow-up. Methods. Data from 166 consecutive OP-CABG patients compared with those of 203 ONpump CABG patients operated on the same time of OP-CABG operations were retrospectively analyzed. Results. As compared to OP-CABG, in the ON-pump CABG patients mean value of Logistic EuroSCORE (8.1%±7.8% vs. 6.2%±5.9%; P<0.05), more extended coronary disease (2.7±0.5 vs. 2.5±0.7 diseased vessels/patient; P<0.001) consequently requiring a greater number of grafts/patient (2.9±0.9 vs. 2.3±0.9; P<0.0001), and emergency surgery (12% vs. 6%; P<0.05) were more frequently observed. Operative mortality was 1.9% in ON-pump CABG vs. 1.2% in OP-CABG (P=NS), incidence of stroke 2.4% vs. 1.8% (P=NS). Incidence of stroke by using OP-CABG PAS-Port system technique was reduced at 1.2%. Intraoperatively, costs per patient were higher for OP-CABG vs. ON-pump CABG (1.930,00 € + 1.050,00 €, if PAS-Port system was included, vs. 1.060,00 € for ON-pump surgery). ICU stay (1.9±1.0 vs. 1.4±0.7 days) and total postoperative in-hospital stay (5.3±3.3 vs. 5.5±3.5 days) were similar in both groups (P>0.1, for both comparisons). At 4 years, survival (91%±13% in the ON-pump CABG vs. 84%±19% in the OP-CABG) and freedom from MACE (composite end-point of all-cause death, myocardial infarction, repeat coronary revascularization of the target lesion) (82%±9% vs. 76%±14%) were not significantly different (P>0.1, for both comparisons). Freedom from late cardiac death was slightly significant higher after ON-pump CABG (98%±4% vs. 90%±10%; P=0.05). Conclusions. Mid-term freedom from composite end-points are substantially similar after ON-pump CABG and OP-CABG. OP-CABG techniques required higher intra-operative costs. Freedom from cardiac death appears to be better after ON-pump CABG.